Determinants of the use of modern contraceptive methods among women of reproductive age in a health zone in southern Benin - Vodouhe, Tchimon Y. S.; Dangbemey, Patrice; Aboubakar, Moufalilou; Boco, Innocent G.; Olowo, Ingrid; Bakary, Samiath M. F.; Bagnan, Angeline Tonato; Denakpo, Justin I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The prevention of unintended pregnancies is one of the essential pillars of reducing avoidable maternal deaths. However, contraceptive prevalence remains low in Benin in general, and particularly in the Allada-Toffo-Zè health zone. Objective was to identify the determinants of the use of modern contraceptive methods among women of reproductive age in the Allada-Toffo-Zè Health Zone. Methods: This was a cross-sectional study with descriptive and analytical purposes, based on prospective data collection from March 6 to May 31, 2023, conducted in ten (10) health facilities within the Allada-Toffo-Zè health zone located in southern Benin. All women of reproductive age (15-49 years old) who attended consultations and provided informed consent were included and interviewed through a face-to-face structured questionnaire. Logistic regression analysis was performed to assess the association between explanatory variables and the outcome variable, which was the use of modern contraceptive methods, with a significance level set at 5%. Results: A total of 402 women were surveyed. The prevalence of modern contraceptive use was 20.79%. The mean age was 28.25±7 years. The determinants of modern contraceptive use were parity (p=0.014), knowledge of the effectiveness of contraceptive methods (p<0.001), knowledge about birth spacing by the method (p<0.001), insurance for the prevention of sexually transmitted infections by the method (p=0.008). Conclusions: Understanding the determinants of modern contraceptive use will help target relevant interventions to improve contraceptive prevalence and contribute to accelerating the reduction of maternal mortality in the health zone.